PENDUGAAN MODEL RANCANGAN CAMPURAN-CAMPURAN DENGAN PETAK TERBAGI - Andriyati, Ani (Fakultas Matematika dan ilmu pengetahuan Alam. Universitas Pakuan.)
Mixture-mixture design with a split plot was proposed for simultaneously two mixture systems. The complete model was formed by multiplying cubic models for two systems. The design was applied to the simultaneous optimizations of both mobile phase chromatographic mixtures and extraction mixture for the Phyllanthus niruri L. In this experiment used split plot approach. Saturated model coefficients were hypothesized with confident interval 99%. Reduction model consisted of real coefficients in complete coefficient models. Estimation method of reduction model coefficients consisted of Ordinary Least Square (OLS) and Generalized Least Square (GLS). Models were formed to count sum peaks chromatographic at 225, 254, and 260 nm. RMSEP values in OLS method at wavelength 225, 254, and 260 nm were produced 4.122, 3.049, and 2.56, otherwise RMSEP values in GLS method were 3.99, 2.79, and 3.18. There are component indicators in wavelength greater and more complex. Key words : Mixture-mixture design, OLS, GLS, split plot